Preparation and In Vitro Evaluation of Alginate Microparticles Containing Amphotericin B for the Treatment of Candida Infections - Alvarez-Berrios, Merlis P.; Aponte-Reyes, Lisa M.; Diaz-Figueroa, Lourdes; Vivero-Escoto, Juan; Johnston, Alexis; Sanchez-Rodriguez, David (International Journal of Biomaterials, 2020)
Invasive candidiasis (IC) remains as a major cause of morbidity and mortality in critically ill patients. Amphotericin B (AmB) is one of the most effective antifungal agents commonly used to treat this infection. However, it induces severe side effects such as nephrotoxicity, cardiac alterations, nausea, fever, and liver damage. The utilization of drug delivery systems has been explored to overcome these limitations. Several AmB lipid formulations have been developed and are currently available in the market. Although they have the ability to reduce the main side effects of free AmB, their high cost, necessity of repeated intravenous injections for successful treatment, and incidence of pulmonary toxicity have limited their use. In the last decades, alginate has gained significant interest in drug delivery applications as a cost-effective strategy to improve the safety and therapeutic effect of toxic drugs. In this work, the clinically relevant drug AmB was encapsulated into alginate microparticles using the emulsification/external gelation method. We hypothesize that this synthesis strategy may positively impact the antifungal efficacy of AmB-loaded MCPs toward Candida albicans cells while reducing the toxicity in human lung cells. To prove this hypothesis, the ability of the microplatform to disrupt the cellular membrane potential was tested and its antifungal effectiveness toward Candida albicans cells was evaluated using the cell counting and plate count methods. Moreover, the toxicity of the microplatform in human lung cells was evaluated using CellTiter 96® AQueous cell viability assay and qualitative diffusion analysis of acridine orange. Our results demonstrated that the platform developed in this work was able to induce antifungal toxicity against Candida albicans yeast cells at the same level of free AmB with minimal toxicity to lung cells, which is one of the main side effects induced by commercial drug delivery systems containing AmB. Overall, our data provides convincing evidence about the effectiveness of the alginate-based microplatform toward Candida albicans cells. In addition, this vehicle may not require several infusions for a successful treatment while reducing the pulmonary toxic effect induced by commercial lipid formulations.